Oxidative Stress and Its Correction in Hemorrhagic Fever With Renal Syndrome - Yu. G. Uskova; V. F. Pavelkina (Антибиотики и Химиотерапия, 2020)
Objective: to investigate the dynamics of indicators of oxidative stress in hemorrhagic fever with renal syndrome (HFRS) accompanied by impaired liver function at different stages of the disease against the background of basic therapy and using Remaxol®. Materials and methods: 67 patients suffering from hemorrhagic fever with moderate renal syndrome were examined: 35 patients of the comparison group received basic therapy, 32 patients of the main group received Remaxol® intravenously, 400 ml 1 time per day, for 10 days, as part of pathogenetic therapy. Results: One of the most important pathogenetic links in HFRS with impaired liver function is the development of oxidative stress. The imbalance in the prooxidant and antioxidant systems persists during the period of clinical recovery and is manifested by an increase in the activity of lipid peroxidation and suppression of antioxidant protection. The presence of hepatic dysfunction aggravates the pathological process, delays patients' recovery and requires not only detoxification and antioxidant use, but also appointment of hepatoprotective agents. Inclusion of Remaxol® in therapy led to a decrease in the severity of clinical symptoms of the disease, hepatic dysfunction (decrease in the activity of the cytolytic syndrome - ALT and AST), shortened the oliguric and polyuric periods of the disease, and contributed to the correction of both primary and secondary products of peroxide homeostasis: diene conjugates, diene cetons, diene kettes. malondialde-hyde plasma, and erythrocytes. Combined therapy increased the activity of antioxidant enzymes - superoxide dismutase, catalase of plasma and erythrocytes. Conclusion: impaired liver function, as well as normalization of the studied indicators of oxidative stress, do not occur during the period of clinical recovery from HFRS. This justifies the need for pharmacological correction of peroxide homeostasis by additional introduction of detoxifying, antioxidant, and hepatoprotective agents to the complex therapy. The use of Remaxol® in the pathogenetic therapy of patients with HFRS reduces the severity of the clinical symptoms of intoxication syndrome, lipid peroxidation processes, the restoration of the body's antioxidant potential, and exerts a hepatotropic effect. Its inclusion in the treatment of HFRS should be considered pathogenetically justified and recommended in clinical practice.